P-031 Mechanical thrombectomy with the solitaire device: is there a learning curve toward achieving rapid recanalization times?. (4th July 2012) - Eesa, M; Almekhlafi, M; Menon, B; Wong, J; Demchuk, A; Goyal, M
Abstract : Introduction/Purpose: We evaluated recanalization times with the Solitaire device in patients undergoing endovascular acute ischemic stroke therapy at our institution. Materials and Methods: We reviewed patients who presented to our stroke center and in whom a Solitaire device was used for revascularization. Demographic data and stroke severity were obtained from chart review. Time points for CT scanning, angiography arrival, puncture, time of first deployment of the device and recanalization times were recorded from time-stamped PACS images and angiography records. Time intervals were calculated (CT to angiography arrival, angiography arrival to puncture, puncture to first deployment and deployment to recanalization). To evaluate time interval trends, recanalized patients were sequentially divided into three sequential groups. Overall CT to recanalization time and interval times between groups were compared using an analysis-of-variance (ANOVA) test. In addition, we also looked for difference between groups using the Scheffe's test correcting for multiple comparisons. All tests are two sided with a p value <0.05 considered to be statistically significant. Analysis was performed using Stata® V.12. Results: 83 patients (38 female; mean age: 65.7±14.3) were treated with the Solitaire device from May 2009 to February 2012. The median NIHSS was 17. Recanalization (TIMI 2/3) occurred in 75 (90.4%) patients. CT to recanalization time showed a statistically significant decrease over time (p<0.01). This difference was maximal between first 25 and most recent 25 cases (161 to 94 min, p<0.01). The maximal contribution to this was from improvements in first deployment to recanalization time between the first 25 and second 25 patients (p=0.01) and between the first and third 25 patients (p=0.001) with modest contributions from moving patients from CT to the angiography-suite faster (p=0.02 between 1st and 3rd groups) and from puncture to first deployment (p=0.02 between 1st and 3rd groups). There was no statistically significant difference in time from angiography-suite arrival to puncture between the groups (Abstract P-031 figure 1 ). Conclusion: There appears to be a learning curve involved in the efficient use of the Solitaire device in endovascular acute stroke therapy. Along with slight improvements in moving patients to angiography sooner and improved efficiency with intracranial access, mastering this device contributed significantly toward the overall drive to reduce recanalization times in stroke patients treated by an endovascular approach at our institution. This needs to be validated in a prospective manner to understand components of this learning curve that is potentially useful to educate new users to achieve faster recanalization times. Competing interests: None.